Faktor pendukung dan penghambat dalam membaca kitab kuning bagi mahasiswa pendidikan bahasa arab - Lewar, Kartika Anggun Adiba (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the supporting and inhibiting factors faced by students of the Arabic Language Education Department in reading kitab kuning (classical Islamic texts). The importance of this research lies in the fact that the ability to read kitab kuning is one of the fundamental aspects of advanced Arabic learning as well as deepening the understanding of Islam. However, many students still face difficulties in this regard. This study employed a descriptive qualitative method, with data collected through interviews and direct observations related to the learning process and students’ experiences in the classroom. The results of the study indicate that the ability to read kitab kuning is greatly influenced by mastery of nahwu and sharaf (Arabic grammar and morphology), prior reading experience, environmental factors such as study groups, and the use of technology. The obstacles identified include weak linguistic foundations, limited vocabulary, low motivation, as well as limited learning resources and an unsuitable learning environment. This study recommends the application of more interactive learning strategies and the provision of supportive learning facilities to improve the skill of reading unvoweled Arabic texts. It is hoped that this research will contribute to improving the quality of Arabic language learning and inspire further, more in-depth and comprehensive studies.